Phytochemical and biological studies on Lindera Oxyphylla and Litsea Costalis (Nees) kosterm (Lauraceae) / Masoumeh Hosseinzadeh - Hosseinzadeh, Masoumeh (2013)
The phytochemical studies on Lindera oxyphylla and Litsea costalis (Nees) Kosterm from the family Lauraceae were performed. The extraction process was carried out using various solvent such as hexane, dichloromethane and methanol and the separation was conducted using column chromatography followed by preparative TLC or PTLC and finally the structural elucidation of isolated compounds was established on the basis of spectroscopic studies such as UV, IR, CD, OR, 1D and 2D NMR and MS (LC-MS) experiments. A total of thirty compounds were isolated from Lindera oxyphylla and Litsea costalis (Nees) Kosterm and these plant species have never been investigated before. From the bark of Lindera oxyphylla yielded six compounds which are (+)-onysilin, (+)-pinostrobin, (+)-pinocenbrin, flavokawain B, linderone and linderone A is a new compound. Seven compounds were isolated from the leaves of this species and these known compounds are one flavanone, kaempferol, one ketone methylinderone, (+)-laurotetanine, N-methyllaurotetanine, (+)-norboldine, (+)-10-O-methyl-N-methylhernovine and (+)-norisoboldine. Nine compounds were isolated from the bark of Litsea costalis (Nees) Kosterm and five known compounds namely cinnamaldehyde, 2-hydroxy-5-methoxybenzaldehyde, 2, 5-dimethoxybenzaldehyde, bisengenol and (E)-4-styrylphenol and four new compounds namely biseugenol A, biseugenol B, biseugenol C and litsin. Eight compounds were isolated from the leaves of this species. These seven known compounds are namely cinnamide, 2, 4-dimethoxybenzamide, 3, 4- dimethoxybenzamide, (+)- pinostrobin, (+)-onysilin, (+)-pinocembrin and 4-allyl-1,2-dimethoxybenzene and one new compound namely costalin. The DPPH experiments for the isolated compounds from Lindera oxyphylla showed the IC50 of LOB15 was 8.5 μg/mL strong activity, LOB4 was 78.97 μg/mL low activity, LOB2 was 41.32 μg/mL low activity, LOB28 was 157.58 μg/mL and LOB25 was 149.45 μg/mL both low activity. The IC50 for the isolated compounds from Litsea costalis (Nees) Kosterm showed that IC50 for LCB17 was 16.34 μg/mL strong activity, LCB15 was 161.81 μg/mL low activity, LCB10 was 81.92 μg/mL low activity, LCB11 was 81.92 μg/mL low activity, LCB3 was 4.77 μg/mL strong activity, LCB7 was 73.24 μg/mL low activity, LCB4 was 26.69 μg/mL strong activity and LCL7 was 76.45 μg/mL low activity. Ascorbic acid was used as a standard with IC50 4.62 μg/mL. The FRAP experiments for the isolated compounds from Lindera oxyphylla showed LOB15 was 1.0 ± 0.06, LOB4 was 0.6 ± 0.01, LOB2 was 0.7 ± 0.02, LOB28 was 0.5 ± 0.02 and LOB25 was 0.5 ± 0.03. Metal chelating assay for the isolated compounds showed LOB15 was 33.37 ± 0.1, LOB4 was 25.69 ± 0.01, LOB2 was 26.11 ± 0.01, LOB28 was 13.09 ± 0.006 and LOB25 was 13.51 ± 0.01. The cytotoxic activity were performed using a series of different doses on A549, PC-3, A375, HT-29, CEMSS, WRL-68, HEPG2, Jurkat and MCF-7 cell lines. The EC50 for LOB4 was 79.57 μg/mL for MCF-7 and 30.12 μg/mL for PC-3, LOB2 showed EC50 for PC-3 was 90.13 μg/mL , LOB25 showed EC50 for MCF-7 was 96.33 μg/mL, LCB17 was 1.4 ± 0.1 μg/mL for MCF-7, 1.0 ± 0.1 μg/mL for HepG2, 1.32 ± 0.1 μg/mL for HT29 and 1.22 ± 0.1 for Jurkat. LCB3 was 48 ± 3.05 μg/mL for MCF-7 and 18 ± 2.1 μg/mL for PC3. The EC50 for LCB10 was 81.73 ± 3.7 μg/mL for WRL68, 1.19 ± 0.19 μg/mL for CEMSS and 85.13 ± 7.3 μg/mL for A549.